THE EFFECT OF CURRENT RATIO (CR), DEBT TO EQUITY RATIO (DER), AND WORKING CAPITAL TURNOVER (WCT) ON RETURN ON EQUITY (ROE) AT PT. INDOCEMENT TUNGGAL PRAKARSA, TBK - Wulandari Wulandari; Wulandari Wulandari; M. Rimawan (Jesya, 2026)
This study aims to determine the effect of Current Ratio (CR), Debt to Equity Ratio (DER), and Working Capital Turnover (WCT) on Return On Equity (ROE) at PT. Indocement Tunggal Prakarsa Tbk for the period 2015–2024. The type of research used is associative quantitative research using the company's financial report data for 10 years. Data analysis techniques used are classical assumption tests, multiple linear regression analysis, correlation and determination coefficients, t-tests, and F-tests with the help of the SPSS version 22 program. The results of the study indicate that Current Ratio (CR) and Debt to Equity Ratio (DER) have a partial significant effect on Return On Equity (ROE), while Working Capital Turnover (WCT) does not have a partial significant effect on Return On Equity (ROE). Simultaneously, Current Ratio (CR), Debt to Equity Ratio (DER), and Working Capital Turnover (WCT) have a significant effect on Return On Equity (ROE). The results of this study indicate that the company's ability to manage liquidity and capital structure has an important role in increasing the company's profitability.